Empire, industry and class: the imperial nexus of jute, 1840-1940 - By Anthony Cox - Camille Buat (The South Asianist, 2014)
From the 1840s onwards, as the commercial success of jute as a packing medium grew, the fortunes of the city of Dundee, the British centre of jute manufacturing, became intertwined with that of one of Britain’s central Indian possession, Bengal. While jute cultivation, and hand manufacture was concentrated in Bengal, successes in the mechanical manufacture of the fibre led to the development of a “jute dependency” in Dundee where jute became the main employer and economic sector. After the setting up of the first jute manufacture in Bengal in 1855, the following decades witnessed the floating of many new companies around Calcutta, with Scottish – and mostly Dundonian – machines and men. By the 1890s Calcutta had become the prime centre of jute manufacture, consigning Dundee to a secondary position.